Рецепція Івана Франка в мемуарних текстах Дмитра Дорошенка - Мазур, Н. (Культура слова, 2016)
У статті на матеріалі «Моїх споминів про давнє минуле (1901-
1914 роки) і «Моїх споминів про недавнє минуле» (1914-1920 рр.)
Д. Дорошенка розглянуто емоційно-оцінну характеристику образу
І. Франка; наведено контексти реалізації лексичної семантики;
відзначено взаємодію образних й емоційно-оцінних лексем; виділено
контексти з оцінною семантикою образу Франка-мислителя,
Франка-інтелектуала, Франка-борця. In the paper the emotionally-estimated characteristic of I. Franko’s
image on the material of Dmytro Doroshenko’s «My memories about the
ancient past» (1901-1914) and «My memories about the recent past»
(1914-1920) is considered; the contexts of lexical semantics realization are
given; the interaction of imaginative and emotionally-estimated lexemes
is distinguished; the contexts with estimated semantics of the image of
Franko-thinker, Franko-intellectual, Franko-fighter are allocated.